Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1136/jitc-2021-sitc2021.389
|View full text |Cite
|
Sign up to set email alerts
|

389 Phase II of CD40 agonistic antibody sotigalimab (APX005M) in combination with nivolumab in subjects with metastatic melanoma with confirmed disease progression on anti-PD-1 therapy

Abstract: BackgroundA significant number of melanoma patients treated with anti-PD-1 alone or in combination with anti-CTLA-4 have transient or no response to treatment. Sotigalimab is a CD40 agonist antibody with unique epitope specificity and Fc receptor binding profile for optimal therapeutic application. Preclinical studies suggest that sotigalimab can be combined with PD-1 blockade to trigger effective anti-tumor immunity. We conducted a multi-center, open label, Phase Ib-parallel arm phase II trial (NCT03123783) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…To enhance potency, the Fc region of some antibodies has been reengineered to potentiate crosslinking (2141-V11 and sotigalimab) [56,64]. Sotigalimab combined with anti-PD-1 treatment, and another optimised CD40-targeting antibody, mitazalimab, combined with chemotherapy have enhanced objective response rates in anti-PD-1-resistant melanoma and pancreatic cancer, respectively [122,123].…”
Section: Pattern Recognitionmentioning
confidence: 99%
“…To enhance potency, the Fc region of some antibodies has been reengineered to potentiate crosslinking (2141-V11 and sotigalimab) [56,64]. Sotigalimab combined with anti-PD-1 treatment, and another optimised CD40-targeting antibody, mitazalimab, combined with chemotherapy have enhanced objective response rates in anti-PD-1-resistant melanoma and pancreatic cancer, respectively [122,123].…”
Section: Pattern Recognitionmentioning
confidence: 99%
“…Combining APX005M with anti-PD-1 blockade to treat anti-PD-1/PD-L1 refractory melanoma patients showed that the combination did not increase toxicity and the majority of adverse events were grade 1 or 2. Early results from the study are promising and indicate that the combination evokes clinical benefit ( 133 ).…”
Section: Targeting Cd40mentioning
confidence: 99%
“…Hence CD40 agonists moAb can play an important role in enhancing APC function for a meaningful and sustained anti-tumor T cell function. Recently, immune check point refractory metastatic melanoma have demonstrated treatment benefit from combination use of CD40 agonistic antibody and nivolumab therapy [ 25 ]. Similarly, CD 40 moab (sotigalimab) had manageable toxicity and an early efficacy signal in a phase Ib pancreatic cancer trial [ 26 ].…”
Section: Immunotherapeutic Agents In Immune Hot and Immune Cold Tumorsmentioning
confidence: 99%